Reliability, validity, and factorial structure of the Turkish version of the Weight Self-Stigma Questionnaire (Turkish WSSQ). Issue 4 (2nd October 2017) - Sevincer, Guzin M.; Kaya, Aysenur; Bozkurt, Suleyman; Akin, Ercan; Kose, Samet
ABSTRACT: OBJECTIVE: The Weight Self-Stigma Questionnaire (WSSQ) is a comprehensive instrument for the assessment of weight self-stigma in obesity and has been validated in several languages. The purpose of this study was to examine the psychometric properties and validate the Turkish version of the WSSQ in a sample of severely obese patients in Turkey. METHODS: A cross-cultural adaptation of the WSSQ into Turkish was carried out, strictly according to recommended methods. The questionnaires including the Sociodemographic data form, the WSSQ, Beck Depression Inventory, Beck Anxiety Inventory, Eating Disorder Examination-Questionnaire, Rosenberg Self-esteem Scale, Dutch Eating Behavior Questionnaire Emotional Eating Subscale, and Impact of Weight on Quality of Life Questionnaire were completed by 120 consecutive severely obese patients (96 female, 24 male) in the outpatient clinics of the Department of Bariatric and Metabolic Surgery in a university setting in Turkey. All statistical analyses were performed by using SPSS version 23 for Windows. RESULTS: The Cronbach's α (internal reliability) for the two subscales of the WSSQ-self-devaluation and fear of enacted stigma, and for the whole questionnaire (WSSQ Total) were 0.74, 0.81, and 0.83, respectively. The self-devaluation subscale, the enacted stigma subscale and the total WSSQ have a good internal consistency. Construct validity also appeared adequate as the WSSQ correlates with other measures largely in the manner we expected. Principal component factor analyses revealed a two-factor structure with an almost identical factor structure to that reported in the original study. Kaiser–Meyer–Olkin Measure of Sampling Adequacy was found to be 0.81 and Barlett's test of Sphericity χ 2 was found as 457.068 ( p  < .01). CONCLUSIONS: Our results suggested that Turkish WSSQ was a valid and reliable tool with a robust factorial structure to use for measuring weight-related self-stigma in clinical population in Turkey.